Research methods for understanding child second language development - Lu, Danni; Li, Tao (Studies in Second Language Learning and Teaching, 2024)
This book offers a comprehensive overview of research methods and techniques specifically tailored for child second language development, an under-explored area in broadly SLA. It is of great pedagogical value that it includes many case studies that illustrate the ways the methods are used in a step-by-step manner, particularly to practitioners, i.e., language teachers at primary schools. This book is a timely and valuable contribution, which is very helpful to both experienced researchers and new beginners, and thus worthy of recommendation.